POWER ENERGY DISTRIBUTION AND CONSUMPTION IN NIGERIA: THE WAY FORWARD FOR SUSTAINABLE INDUSTRIAL AND COMMERCIAL DEVELOPMENT (Nigerian Journal of Technology, 2020)
The wasteful, non-efficient way and manner in which the small, available power energy in Nigeria is distributed and consumed especially by residential consumers, is such that it cannot grow the country sustainably. The result is that Nigeria will continue to remain a developing economy with the associated features. This paper examines the current electricity distribution and consumption scenario in Nigeria and also discusses the myriads of problems associated with the distribution and consumption of power energy in the country. Available data and findings presented in this paper show that distribution of electricity is bedeviled with high losses and is corruption ridden while consumption is wasteful and non-efficient. The paper makes some suggestions on the way forward for Nigeria to grow sustainably. The paper concludes that unless the current electricity distribution and consumption patterns are reversed and re-patterned, industrial and commercial advancement will continue to elude the nation. The paper recommends the way forward on how to re-position the power energy sub sector of the economy so as to achieve sustainable national development.  http://dx.doi.org/10.4314/njt.v39i3.27